Simulation of the management method for producing bridge elements in precasting yard - Ooi, Jit Cheow. (2009)
This thesis concentrates on the study of using computer simulation in the management of a precasting yard producing bridge elements. For this purpose, a computer model simulation was built to simulate the management of material flow and logistic planning pertaining to the precasting yard such as beam casting operation, beam launching operation, site storage constraints and resources required for each activity. The simulation model is used as a vehicle for experimentation, in a way to demonstrate the likely effects of various activities on to the project duration as well as on to one another. The results obtained are then analysed and tested against actual data.